Why Putting On Blinders Can Help Us See More Clearly - Fath, Sean; Fath, Sean; Larrick, Richard; Soll, Jack; Zhu, Susan (MIT Sloan Management Review, 2021)
Only certain details about job candidates are relevant for hiring decisions; knowing other details can undermine the fairness and accuracy of employers' assessments. Organizations can establish policies that “blind” decision makers to potentially biasing information, but this is rare. This article looks at when managers and other evaluators might choose to blind their own judgment and suggests ways they can foster less-biased decision-making in their organizations.